Hydrologic modeling of San Juan River basin using HEC-HMS - Castillo, Jayveen P.
Urban flooding poses great risks to the population and the economy, thus, it is necessary to pursue flood mitigation efforts using combined hydrologic-hydraulic modelling of major rivers in the country. This study aims to develop a hydrologic model for the San Juan River basin using Hydrologic Engineering Center - Hydrologic Modeling System (HEC-HMS) to produce stream hydrographs by simulating historical and hypothetical storms. The SCS Curve Number method was used to account for precipitation losses, the Kinematic Wave Transform Model for rainfall-runoff transformation, and the Kinematic Wave Routing Model for channel routing. Necessary data and information were gathered, and physical parameters were processed using QGIS. The model was calibrated using observed hydrographs during a storm event and was found to yield good results with 0.17% and 16.79% error on the simulated volume and peak discharge, respectively - more conservative than the latest model developed in 2013. Frequency storms were utilized to simulate flooding scenarios over the watershed. Hydrographs were obtained at strategic points along the streams which were used as boundary conditions for a hydraulic study on the river Over-all , HEC-HMS is a good platform for the synthesis of hydrologic models - essential for storm and flood preparedness, in frastructure design and risk assessment, and urban development.